First vs. multiple cannabis-induced psychotic episodes: Is inpatient treatment any different?. (13th April 2021) - Andrade, F.; Covelo, V.; Machado, A.S.
Abstract : Introduction: Recent studies reported very high cumulative risk for a patient who had cannabis-induced psychosis to be diagnosed with a schizophrenia spectrum disorder. Objectives: We aim to compare sociodemographic and clinical characteristics, treatment and discharge plan in cannabis-induced first psychosis episode (CI-FEP) vs. multiple cannabis-induced psychotic episodes (CI-MEP) inpatients. Methods: Retrospective observational study of inpatient episodes with a discharge diagnosis of cannabis-induced psychosis between January 1 st, 2018 and December 31 st, 2019 in the Psychiatry Service of CHUSJ. Descriptive analysis of the results was performed using the SPSS software, version 26.0. Results: Our sample included 61 inpatients, 19 (31.1%) with CI-FEP and 42 (68.9%) with CI-MEP. CI-MEP group had a median of 1±0, 234 previous hospital admissions. CI-MEP group has 10, 0 higher odds of being discharged in outpatient compulsory treatment (CI 95% 1, 21-82, 50, p=0, 013) and 6.0 odds of being treated with long-acting injectable antipsychotics (LAIAP) (CI 95% 1, 79-20, 31, p=0, 002) when compared to CI-FEP group. Having multiple cannabis-induced psychotic episodes was associated with future admissions to psychiatry unit (OR 4, 85 (95% CI 1, 23-19, 15, p=0, 018). We found no statistically significant differences regarding the sociodemographic and clinical characteristics, use habits and discharge plan between the two groups. Conclusions: Patients with multiple psychotic episodes due to cannabis use are more likely to have a LAIAP prescription, be discharged in compulsory outpatient regimen and be readmitted in to psychiatric inpatient unit. Considering the prevalence of CI-MEP and the risk of chronicity, we need integrative treatment programs to address the specificities of these patients.